The impact of random porosity distribution on the composite metal foam-phase change heat transfer for thermal energy storage - Fteiti, Mehdi A.; Ghalambaz, Mehdi; Sheremet, Mikhail A.; Ghalambaz, Mohammad (Journal of energy storage)
The goal of this work is to investigate the phase change material (PCM) embedded with a high thermal conductive solid structure (metal foam). In order to boost the effective heat conductivity and therefore quicken the storage process, metal foam is incorporated. The resultant storage medium is handled as a porous material. Most of earlier investigations of a similar type assumed that the medium's porosity in the porous zone is uniform. However, a random porosity is more accurate and realistic. Various sets of random structures were created using a pseudo-random generator. The mathematical formulation utilizes the Darcy-Brinkman model and volume-averaging method. The governing equations are numerically solved using the control-volume-based finite element approach. Various samples with high random porosity distributions were simulated and compared to the case of uniform porosity. The results were reported in the form of isotherms, liquid fractions, and streamlines. The outcomes revealed that a random porous medium could provide a lower rate of PCM melting (up to 10 %) for a similar average porosity compared to a uniform porous medium.